A retrospective comparative study on arthroscopic suture anchors repair and tendon debridement versus arthroscopic tendon debridement for treatment of recalcitrant lateral epicondylitis. (April 2021) - Li, Xu; Zheng, Tong; Li, Yue; Zhang, Hailong; Lu, Yi
Aim: To compare the outcomes between the arthroscopic debridement of the extensor carpi radialis brevis (ECRB) tendon alone and repairs to the ECRB tendon with suture anchor for the treatment of refractory lateral epicondylitis (LE). Methods: We retrospectively reviewed our patients who underwent arthroscopic surgical treatment for refractory LE by a single surgeon from January 2008 to June 2018 with a minimum follow-up of 12 months. The visual analog scale (VAS), the Mayo Elbow Performance Score (MEPS), the Disability of the Arm, Shoulder, and Hand (DASH) questionnaire, the Patient-Rated Tennis Elbow Evaluation (PRTEE) scale, the Verhaar scoring system and the time of back to work were compared between two groups. Results: Both groups showed a significant postoperative improvement regarding the VAS, MEPS, DASH, PRTEE and the Verhaar scoring system ( p  < 0.05). The repair group showed better results regarding the MEPS, DASH, PRTEE and Verhaar scoring system comparing with the debridement group, which were statically significant ( p  < 0.05). There were no significant differences between the two groups regarding the VAS both at rest and activity at the final follow-up. There were no significant differences for the average time for return to work ( p  = 0.229). There were 11 patients in the debridement group and six patients in the repair group, who completed the MRI evaluation at 6 months postoperatively. Conclusion: Compared with arthroscopic release and debridement of the ECRB tendon, arthroscopic suture anchor repairing of the origin of the ECRB tendon provides better outcomes when addressing the refractory LE. Level of Evidence: Case Series: Level IV